GENETIC DIVERGENCE IN CULTIVATED POTATO GERMPLASM - Regassa, Dereje; Basavaraja, N (Potato Journal, 2013)
One hundred potato genotypes were grown under rain-fed condition at Dharwad and evaluated for presence of genetic diversity using Mahalanobis D2 analysis. The D2 analysis grouped all genotypes into 8 clusters. Source of the genotypes had no relation with genetic diversity. Average tuber weight per plant registered the maximum relative contribution to total divergence followed by number of main stems per plant.